2008
DOI: 10.1007/s00421-008-0799-2
|View full text |Cite
|
Sign up to set email alerts
|

Stretch and sprint training reduces stretch-induced sprint performance deficits in 13- to 15-year-old youth

Abstract: The recently reported static stretching impairments found in adults have not been studied in youth. Furthermore, stretch-training effects on sprint performance are equivocal, hence the purpose of this study was to examine the effect of stretch and sprint training on the acute effects of static stretching in 13-15 year olds. A total of 48 students were randomly divided into a sprint only and a stretch and sprint training groups who performed static stretching at the beginning and middle of the speed training se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…The results are in agreement with previous findings (Fletcher and Anness,2007, Fletcher and Jones, 2004, Little and Williams, 2006Nelson et al, 2005, Chaouachi et al, 2008, Paradisis et al, 2013, Vasileiou et al 2013, Papadopoulos et al, 2015, Famisis, 2015. Similar were the CMJ results.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The results are in agreement with previous findings (Fletcher and Anness,2007, Fletcher and Jones, 2004, Little and Williams, 2006Nelson et al, 2005, Chaouachi et al, 2008, Paradisis et al, 2013, Vasileiou et al 2013, Papadopoulos et al, 2015, Famisis, 2015. Similar were the CMJ results.…”
Section: Discussionsupporting
confidence: 93%
“…www.efsupit.ro 220 and sprint (Alikhajeh et al 2012, Chaouachi et al 2008, Fletcher & Jones 2004, Fletcher & Monte-Colombo 2010, Gelen 2010, Needman et al 2009, Sayers et al 2008, Winchester et al 2008. Papadopoulos et al 2015 have been previously reported as a result of static stretching.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Indeed, some studies insisted that static stretching could contribute to injury prevention through improvement of range of motion (ROM) in the applied joint (Shellock and Prentice 1985;Smith 1984;Young and Behm 2002). On the other hand, recent studies suggest that passive static stretching decreases not only the muscle strength and power output (Babault et al 2010;Cramer et al 2005;Fowles et al 2000;Kokkonen et al 1998;Marek et al 2005;McBride et al 2007), but also running performance (Chaouachi et al 2008;Fletcher and Anness 2007;Stewart et al 2007).…”
Section: Introductionmentioning
confidence: 95%